Padam in Historical Perspective - Suhanya, A. (International Research Journal of Tamil, 2022)
It is a fact of history that songs have appeared in Tamil art culture from time to time and have enriched the arts. Language and art are generally interdependent within the cultural elements of a community. In this way, it is possible to know through the histories that the genres of songs have changed without any change in the cultural changes that have taken place in the history of music and dance in Tamil Nadu from time to time. This article is intended as a historical overview of the genre of Padam, an item that is considered important in the Carnatic music and Bharatanatyam tradition. This article will annualize about what we mean by term, the source, content, usage of this term and other aspects in Padam.
Keywords: Padam; Uruppadi; Chrunkaram; Intro songs; Intuition; Artistry